ANALISIS NILAI-NILAI PSIKOLOGIS HUKUM ISLAM DALAM WASIAT - Khairil Anwar; Irsan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2022)
This study analyses the psychological values in the law of will. This research is library research, and the data analysis technique in this research is content analysis. Psychology is the science of the soul, mind and behaviour, and what is meant by psychological values of Islamic law are the psychological values contained in every law in Islam, whether the law is in the form of words or deeds. This study concludes that the psychological values contained in law of will are motivation for people who are going to die to always think positively in Allah, motivation for parents to think about the future of their children, motivation for heirs to be content for the calamity that befell them, motivation for heirs to be generous descendants, and motivation for heirs to always maintain harmony in family.